A new species of Cyrtodactylus Gray, 1827 (Squamata, Gekkonidae) from Yunnan, China - Liu, Shuo (Zookeys, 2021)
A new species of Cyrtodactylus is described on the basis of five specimens collected from the karst formations of Zhenkang County, Yunnan Province, China. Cyrtodactylus zhenkangensissp. nov. is recognized by having a unique combination of morphological characters, the most diagnostic being: 12–15 enlarged femoral scales on each thigh; 2–5 femoral pores on each thigh in males, 0–3 pitted scales on each thigh in females; eight or nine precloacal pores in a continuous row or separated by one poreless scale in males, 7–9 pitted scales in females; subcaudals enlarged, arranged alternately as single and double on anterior and mostly single at middle and posterior; dorsal surface of head with obvious reticulations. Phylogenetic analyses show that the new species is a member of the C. wayakonei species group and a sister taxon to a clade consisting of C. wayakonei and C. martini based on Maximum Likelihood analyses and Bayesian Inference and differs from its congeners by at least 12.0% genetic divergence in a fragment of the COI gene.